2003
DOI: 10.1086/367786
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the Ionization Balance of Hot‐Star Winds fromFUSEObservations of O Stars in the Large Magellanic Cloud

Abstract: We present Far Ultraviolet Spectroscopic Explorer (FUSE) spectra for 25 O stars in the Large Magellanic Cloud (LMC). We analyze wind profiles for the

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
138
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(155 citation statements)
references
References 65 publications
(86 reference statements)
14
138
2
1
Order By: Relevance
“…6 the predicted ionization fractions in comparison with those derived from observation as a function of effective stellar temperature. Note that here we use the ionization fractions derived for LMC stars (Massa et al 2003), because their observational sample includes a large number of ionization stages, the fractions of which are given as a function of velocity, and the wind parameters of LMC stars are not significantly different from Galactic ones. Since several parameters except the effective temperature (e.g., the wind density) may influence the ionization fractions, the graphs in Fig.…”
Section: Ionization Fractionsmentioning
confidence: 99%
“…6 the predicted ionization fractions in comparison with those derived from observation as a function of effective stellar temperature. Note that here we use the ionization fractions derived for LMC stars (Massa et al 2003), because their observational sample includes a large number of ionization stages, the fractions of which are given as a function of velocity, and the wind parameters of LMC stars are not significantly different from Galactic ones. Since several parameters except the effective temperature (e.g., the wind density) may influence the ionization fractions, the graphs in Fig.…”
Section: Ionization Fractionsmentioning
confidence: 99%
“…The observed mass-loss rates may be influenced by wind clumping (e.g. Crowther et al 2002;Massa et al 2003;Bouret et al 2003) and thus, the observed mass-loss rates shall be lower in such a case (see also Kramer et al 2003, for the discussion of effect of clumping on the theoretical profiles of X-ray lines). However, in such a case clumping would influence also the theoretical mass-loss rates (cf.…”
Section: Mass Loss Ratesmentioning
confidence: 99%
“…Fullerton: Very similar discrepancies are seen in samples of O-type stars observed with FUSE in both the LMC (Crowther et al 2002, Massa et al 2003 and SMC (Hillier et al 2003). Although these samples are limited, they don't provide any evidence to suggest that the degree of clumping depends strongly on the overall metallicity of the star.…”
Section: Discussionmentioning
confidence: 89%
“…5 shows that measurements ofṀ from ρ 2 diagnostics for a "blue-ribbon" sample of 40 Galactic O-type stars are always greater than measurements from the P v resonance lines by a factor of at least 20 (Fullerton, Massa, & Prinja 2006). Detailed model atmosphere calculations indicate similar levels of disagreement between Hα and the P v doublet for O-type supergiants in the Galaxy (Bouret et al 2005), Large Magellanic Cloud (Crowther et al 2002;Massa et al 2003) and Small Magellanic Cloud (Hillier et al 2003).…”
Section: Discrepant Mass-loss Estimatesmentioning
confidence: 88%